THE RELATIONSHIP BETWEEN MOTHERS' FEEDING SELF EFFICACY AND STUNTING PREVENTION BEHAVIOR - Hasiolan, Mara Imbang Satriawan; Wada, Fauziah H; Sunirah, Sunirah (Nursing Genius Journal, 2025)
Background:  Background: Stunting occurs in children aged 0-59 months, caused by nutritional problems during pregnancy or infancy. Therefore, nutrition in the first year of life, namely breast milk and complementary foods, must be considered early and from the first time it is given. Self-Efficacy is one of the factors that shape maternal behavior in supporting nutrition given to toddlers. Good self-efficacy can support the formation of stunting prevention behavior and can improve health. Self-efficacy is the mother's trust and confidence in carrying out complementary feeding activities, by providing food at the right time and in sufficient quantities, frequency, composition, and variety, providing safe food, creating a comfortable environment when eating, and providing appropriate responses to eating behavior in children. Purpose: To determine the relationship between maternal feeding self-efficacy (MP-ASI) and stunting prevention behavior in the Kedung Waringin Community Health Center (Puskesmas) working area, Bekasi Regency. Methods:This study used a quantitative cross-sectional approach, using primary data. The study population was 119 mothers with toddlers in the Kedung Waringin Community Health Center working area. The sampling technique used was purposive sampling. Data collection used the CFSE and Stunting Prevention Behavior questionnaires. Data were analyzed using chi-square. Results:The relationship between feeding self-efficacy and stunting prevention behavior obtained a p-value of 0.154 > α = 0.05. Conclusion: There was no relationship between maternal feeding self-efficacy and stunting prevention behavior in the Kedung Waringin Community Health Center working area, Bekasi Regency.